PhyTB: Phylogenetic tree visualisation and sample positioning for M. tuberculosis. Issue 1 (December 2015) - Benavente, Ernest; Coll, Francesc; Furnham, Nick; McNerney, Ruth; Glynn, Judith; Campino, Susana; Pain, Arnab; Mohareb, Fady; Clark, Taane
Abstract Background Phylogenetic-based classification ofM. tuberculosis and other bacterial genomes is a core analysis for studying evolutionary hypotheses, disease outbreaks and transmission events. Whole genome sequencing is providing new insights into the genomic variation underlying intra- and inter-strain diversity, thereby assisting with the classification and molecular barcoding of the bacteria. One roadblock to strain investigation is the lack of user-interactive solutions to interrogate and visualise variation within a phylogenetic tree setting. Results We have developed a web-based tool calledPhyTB (http://pathogenseq.lshtm.ac.uk/phytblive/index.php ) to assist phylogenetic tree visualisation and identification ofM. tuberculosis clade-informative polymorphism. Variant Call Format files can be uploaded to determine a sample position within the tree. A map view summarises the geographical distribution of alleles and strain-types. The utility of thePhyTB is demonstrated on sequence data from 1, 601M. tuberculosis isolates. Conclusion PhyTB contextualisesM. tuberculosis genomic variation within epidemiological, geographical and phylogenic settings. Further tool utility is possible by incorporating large variants and phenotypic data (e.g. drug-resistance profiles), and an assessment of genotype-phenotype associations. Source code is available to develop similar websites for other organisms (http://sourceforge.net/projects/phylotrack ).